Impact of different hemodiafiltration solutions on ionemia in long-term CRRT. Issue 11 (November 2021) - Nalesso, Federico; Garzotto, Francesco; Cattarin, Leda; Innico, Georgie; Gobbi, Laura; Calò, Lorenzo A
Critical patients with Acute Kidney Injury (AKI) requiring renal replacement therapy are in most cases eligible only for continuous modalities where the electrolyte balance control is a critical issue. The standard solutions used for hemodiafiltration, containing potassium at 2 mmol/L and no phosphorus, determines during the extended renal replacement therapy hypokalemia and hypophosphatemia. Therefore, solutions containing potassium and phosphate in physiological concentrations were formulated to avoid electrolyte imbalances and reduce ion alterations in prolonged treatments, these solutions are not routinely used in the standard clinical practice. To avoid electrolyte imbalances, we have first introduced in our practice two different solutions and then we have retrospectively analyzed the electrolyte balance upon these two solutions in order to identity the impact of these solutions on potassium and phosphate according to our clinical practice. We retrospectively analyzed 96 patients treated with Continuous Renal Replacement Therapy (CRRT) in the intensive care units (ICU) at Padua's University Hospital to evaluate the role on electrolyte balance of Phoxilium ® and Prismasol 2 ® that differ in their composition and the need for electrolytes infusions. In the Phoxilium group the frequency of hypokalemia, hypophosphatemia, and the need of potassium and phosphate replacement were significantly reduced resulting in a reduction in complications, workload, and clinical risk associated with infusions of electrolytes. Our data demonstrated that the use of these two different hemodiafiltration solutions can reduce the occurrence of hypokalemia and hypophosphatemia during CRRT performing personalized treatments without the use of potassium and phosphate infusions.